Missed opportunities for diagnosing primary HIV infection. Issue 1 (30th October 2007) - Sudarshi, D; Pao, D; Murphy, G; Parry, J; Dean, G; Fisher, M
Abstract : Objective: To investigate the extent to which primary HIV infection (PHI) presents to healthcare providers and the degree to which it is unrecognised. Methods: All individuals diagnosed with having recent HIV infection between 2003 and 2005 were identified (based on the following criteria: an evolving antibody response, negative HIV test within 18 months or a serological testing algorithm for recent HIV seroconversion). Symptoms of PHI and previous presentation to other healthcare providers were ascertained from HIV clinic notes and laboratory records (a single laboratory performing all of the HIV tests in the area). Results: Of the 108 subjects, 103 (95%) were male and 93 (86%) were men who had sex with men. A total of 76 of the 108 individuals (70%) reported symptoms of seroconversion. Of these, 40 (53%) presented to a healthcare provider during the symptomatic period. Of these, 21 (52%) were diagnosed with having PHI at first presentation. In the 19 patients (48%) in which a diagnosis of having PHI was not made at first presentation, 15 were seen in primary care, 3 in accident and emergency, and 1 in genitourinary medicine (GUM). Conclusions: The diagnosis of PHI is often missed. Individuals in high-risk groups need to be informed to access healthcare when they experience symptoms of seroconversion. Non-HIV/GUM healthcare providers (especially primary care) may benefit from training in case recognition to improve rates of diagnosis.